The ability of the Lab4 probiotic consortium to impact upon the functionality of serum deprived human keratinocytes in vitro - Thomas, Sophie E.; Kerry-Smith, Joshua; Plummer, Susan F.; Bate, Jack P.; John, Daniel A.; Lawrence, Evie; Powell, Lydia; Dally, Jordanna; Moseley, Ryan; Michael, Daryn R. (Frontiers in Microbiomes, 2024)
IntroductionDysfunction of keratinocytes contributes to a weakened skin barrier and impaired wound healing capability. Evidence suggests that probiotic supplementation can lead to improved skin function in vitro and in vivo. The Lab4 probiotic consortium comprises of two strains of Lactobacillus species and two strains of Bifidobacterium species.MethodsUsing serum deprived conditions to impair the functionality of immortalized human HaCaT keratinocytes, this study aimed to assess the impact of metabolites derived from the Lab4 probiotic consortium on keratinocyte function.ResultsA significant improvement in HaCaT metabolic activity and lower apoptotic activity was observed in tandem with a reduction in Caspase-3 gene expression and a lower Bax/Bcl2 ratio following the addition of Lab4. The probiotic also supported barrier integrity which was better maintained with a significant increase in Filaggrin gene expression. In damaged keratinocytes, Lab4 enhanced rates of re-epithelialization, which were associated with significantly increased gene expression of MMP-1 and enhanced secretion of IL-6 and IL-8.DiscussionThese results suggest that the Lab4 probiotic consortium may have the ability to benefit the functionality of skin.